KONTRIBUSI MOTIVASI BERPRESTASI DAN KONSEP DIRI TERHADAP KEGIATAN MERESPON DALAM PEMBELAJARAN SERTA IMPLIKASINYA DALAM BIMBINGAN DAN KONSELING - Rizky Andana Pohan; Rini Hayati Hayati; Dika Sahputra Sahputra (Faculty of teaching training and education, 2018)
This research was conducted by the still variability of data about studentsÃ¢â‚¬â„¢ responding activity when learning in a class. The achievement motivation and self-concept were two factors assumed to affect responding activity in learning. This research is aimed to describe the contribution of the achievement motivation and self-concept towards responding activity in learning. This research applied quantitative method with a descriptive correlational. The population of this research were 700 students of SMA Negeri 1 Percut Sei Tuan in grade Ã‚Â X and XI, and the samples were 254 students that were chosen by using proportional stratified random sampling. The instrument of the research was a likert scale. The dataÃ‚Â were analyzed by using descriptive statistics, simple and multiple regression. The research findings indicated that: (1) averagely, description of the achievement motivation was at high level, (2) self-concept was at positive level, (3)Ã‚Â responding activity in learning was categorized at high level, (4) there was 7.6% (R= 0.276, on significance 0.000) in achievement motivation contribution towardsÃ‚Â responding activity, (5) there was 7.7% (R= 0.279, significance 0.000) in studentsÃ¢â‚¬â„¢ self-concept, (6) there was 11.7% (R= 0.343, on significance 0.000) in contribution together with achievement motivation and self-concept towards responding activity in learning. The implication of this research can be made as a need assessment to make a program of guidance and counseling service in SMA Negeri 1 Percut Sei Tuan.Keywords : Achievement Motivation, Self-Concept, Responding Activity